A Concise History of American Music Education - Mark, Michael (Rowman & Littlefield Publishers, 2008)
A Concise History of American Music Education covers the history of American music education, from its roots in Biblical times through recent historical events and trends. It describes the educational, philosophical, and sociological aspects of the subject, always putting it in the context of the history of the United States. It offers complete information on professional organizations, materials, techniques, and personalities in music education.